2017
DOI: 10.20944/preprints201708.0088.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Development of a Data Set of Pesticide Dissipation Rates in/on Various Plant Matrices for the Pesticide Properties Database (PPDB)

Abstract: Data relating to the rate at which pesticide active substances dissipate on or within various plant matrices are important for a range of different risk assessments; however, despite the importance of this data, dissipation rates are not included in the most common online data resources. Databases have been collated in the past, but these tend not to be maintained or regularly updated. The purpose of the exercise described herein was to collate a new database in a format compatible with the main online pestici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…The formation rate of FSN in soil (PSL and PRZ) used in the simulations was calibrated to the value of 25% (Table ) which is consistent with the literature where the maximum formation ratio of FSN in soil was reported as not exceeding 34.3% . The observed concentrations of FSN peaked three days after the application of fipronil in PW and PSL for the two monitoring years (Figs c,d and c,d).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The formation rate of FSN in soil (PSL and PRZ) used in the simulations was calibrated to the value of 25% (Table ) which is consistent with the literature where the maximum formation ratio of FSN in soil was reported as not exceeding 34.3% . The observed concentrations of FSN peaked three days after the application of fipronil in PW and PSL for the two monitoring years (Figs c,d and c,d).…”
Section: Resultssupporting
confidence: 71%
“…The input parameters used to forecast the concentrations of fipronil were selected to be identical to those reported during the validation of the PCPF‐NB model . Input parameters for the metabolites FSN and FD were extracted from the literature or calibrated when no data were available . The input parameters used in the PCPF‐M model for forecasting the concentrations of fipronil and its metabolites in PW are presented in Table while the forecasted and observed concentrations of fipronil, FSN and FD are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in line with observations in the present study, in which marked differences were observed between trials. Lewis and Tzilivakis () stressed the importance of keeping a database on foliar half‐lives up to date because the portfolio of chemicals constantly changes.…”
Section: Discussionmentioning
confidence: 99%
“…The exponential decay equation helps to significantly predict the half-life of individual pesticides as well as the theoretical residue of the target pesticide in a plant at a specific time. 18) In addition, studies elsewhere have developed different dissipation models of pesticides in soil or plants using either bi-exponential or mono-exponential models. The review conducted by Fantke and Juraske 19) provided an overview of nine kinetic models to predict pesticide-dissipation half-lives in plants.…”
Section: Introductionmentioning
confidence: 99%